Development of lanthanum cerate based thermal barrier coatings with enhanced resistance to ingestion by volcanic ash particles. (February 2022) - Praveen, K.; Shanmugavelayutham, G.; Srinivasa Rao, D.; Sivakumar, G.
Abstract: Lanthanum cerate (LC) is one of the potential candidates for thermal barrier coatings (TBCs) by virtue of its high melting point and favorable thermophysical properties. Infiltration of silicate in LC coating was found to be effectively arrested by forming La-Ce apatite. To qualify LC based material for next-generation TBCs, it is essential to understand the role of rare earth oxides (REOs) dopants that can manage the thermal expansion coefficient values and provides improved performance in volcanic ash infiltration resistance. Accordingly, various REOs doped LC was synthesized, plasma sprayed to generate free-standing coupons, and evaluated their volcanic ash infiltration resistance. Graphical Abstract: ga1 Highlights: LC and REOs doped LC powders are prepared by solid-state reaction method, coatings were fabricated by APS. Synthesized powders, coatings and 100 hrs heat-treated coatings at 1250 °C showed a stable phase without any impurities. VA mitigation shows all the LC based coatings resist the infiltration of VA by forming an apatite phase sealing layer. Y-LC coating has the least infiltration among different coatings compared to Yb-LC, Gd-LC and LC compositions. The microhardness of the sealing layer was doubled to that of the as-deposited coating in LC based coatings.